DAYA ANTIMIKROBA EKSTRAK Lecythophora sp., ENDOFIT YANG DIISOLASI DARI Alyxia reinwardtii - Noor Erma Sugijanto; H. Putra; F. Pritayuni; N. Albathaty; Noor Cholies Zaini (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
The antimicrobial potential of two endophytic fungi isolated from Alyxia reinwardtii BL, towards selected bacteria (Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Bacillus subtilis FNCC 0059, Pseudomonas aeruginosa ATCC 27853, Salmonella typhi) and fungi (Candida albicans) was tested using ethyl acetate, n-hexane and n-buthanol extracts of fungi cultivated under malt extract liquid fermentation. The extracts were evaluated for its antimicrobial activity by disc diffusion method followed its MIC by agar dilution. Bioautography assay for activity-directed fractionation were also conducted against Bacillus subtilis and Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922. Streptomycin sulphate and myconazole used as reference standards. Lecythophora sp. strain 30.1 and 30.5 have broad spectrum antimicrobial activity and a potential source of new classes of antibiotics that could be useful for medicines and biological control agents.